The Mystery of the Disappearing Nasal Packs - Yew Richard, Wong Kim; Rasheed, Shamim Rahman Bin SMA Abdul (International Journal of Human and Health Sciences (IJHHS), 2022)
Nasal packing is commonly used for hemostasis post nasal surgeries. It is cheap, easily available and is routinely practiced in many centres. However, they may be associated with complications. Some of the complications include pain during nasal packing removal, damage or injury to the nasal mucosa leading to synechiae formation, crusting, and septal perforation. We describe a case of a 39-year-old gentleman who underwent a septoturbinoplasty procedure, to address his nasal problem and subsequently nasal packing was inserted into bilateral nasal cavity for hemostasis. However, prior to extubation, it was noted that the nasal packing were not in situ. Nasoendoscopy and direct laryngoscopy were performed but were unable to trace the missing nasal packs. An Oesophagogastroduodenoscopy (OGDS) was done and revealed the presence of the nasal packing in the stomach. This case highlighted the risk of nasal packing to be dislodged from the nasal cavity into the stomach if not secured properly, and therefore we recommended securing the nasal packing in its position by tying a knot using the strings attached with the nasal packing together. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 442-444